mFOLFOXIRI versus mFOLFOX6 as neoadjuvant chemother apy in locally advanced rectal cancer:a propensity score matching analysis - Qiu Meng (结直肠肛门外科)
[Background] Preoperative chemoradiotherapy (CRT) is the standard treatment for locally advanced rectal cancer (LARC). However, CRT failed to impact metastatic recurrence and the risk of side effects on bowel and genitourinary remained a concern. Neoadjuvant chemotherapy alone with mFOLFOX6 or FOLFOXIRI had been investigated in LARC. Here, we tried to compare the efficacy of mFOLFOXIRI with mFOLFOX6 as neoadjuvant chemotherapy in LARC. [Patients and methods] Between January 2014 and December 2019, patients with LARC receiving neoadjuvant chemotherapy with mFOLFOXIRI or mFOLFOX6 were retrospective analyzed, including data from a prospective trial (NCT02217020). All patients underwent total mesorectal excision (TME). The propensity-score matching was preformed to adjust baseline potential confounders and to estimate differences in outcomes between patients receiving mFOLFOXIRI and mFOLFOX6. Survival analysis was done using Kaplan-Meier analysis and Cox proportional regression analysis. [Results] The median follow-up time was 31.1 months. After propensity score matching, 156 patients were available for comparison in each group. The pathological complete response (pCR) rate was 17.9% vs. 5.1% (P<0.001), the incidence rate of anastomotic fistula was 3.2% vs. 9% (P=0.03), the 3 year disease-free survival (DFS) rate was 75% vs. 66.7% (P=0.047) and the distant metastasis rate was 16.4% versus 26.6% (P=0.013) for mFOLFOXIRI and mFOLFOX6 group, respectively. Patients receiving mFOLFOXIRI had higher incidence of grade III and/or IV nausea and/or vomiting (7.6% vs. 2.5%, P=0.04). [Conclusions] Neoadjuvant mFOLFOXIRI regimens improved pCR rate and survival outcome, reduced the rate of distant metastasis and anastomotic fistula when comparing with propensity-score matched controls of mFOLFOX6 neoadjuvant chemotherapy. [Microabstract] This trial assessed the short-term and long-term effects of neoadjuvant chemotherapy with mFOLFOXIRI and mFOLFOX6 in patients with locally advanced rectal cancer. Comparing with propensity-score matched historical control of chemoradiotherapy, neoadjuvant mFOLFOXIRI chemotherapy was well tolerated and led to higher rates of 3 year disease-free survival in patients with locally advanced rectal cancer.